Stimulation of innate immunity by host and viral RNAs - Streicher, Felix; Jouvenet, Nolwenn (Trends in immunology, 2019)
The interferon (IFN) response, a major vertebrate defense mechanism against viral infections, is initiated by RIG-I-like receptor (RLR)-mediated recognition of viral replicative intermediates in the cytosol. RLR purification methods coupled to RNA sequencing have recently led to the characterization of viral nucleic acid features recognized by RLRs in infected cells. This work revealed that some cellular RNAs can bind to RLRs and stimulate the IFN response. We provide an overview of self and non-self RNAs that activate innate immunity, and discuss the cellular dysregulation that allows recognition of cellular RNAs by RLRs, including RNA mislocalization and downregulation of RNA-shielding proteins. These discussions are relevant because manipulating RLR activation presents opportunities for treating viral infections and autoimmune disorders.